Solve this:-
![2(x - 7) + 10 = 2x + 7(x + 1)for \: x 2(x - 7) + 10 = 2x + 7(x + 1)for \: x](https://tex.z-dn.net/?f=2%28x+-+7%29+%2B+10+%3D+2x+%2B+7%28x+%2B+1%29for+%5C%3A+x)
××No spamming××
♨️Juniors stay away♨️
Answers
Answered by
1
Answer:
Step-by-step explanation:
Hope you got your Answer...
Have a nice Day
Answered by
2
2(x-7)10=2x+7(x+1)
2x-14+10=2x+7x+7
2x-4=9x+7
7x=-11
x=-11/7
hope it hlps you
ok yaar
Similar questions
English,
2 months ago
Hindi,
2 months ago
Math,
2 months ago
Science,
4 months ago
CBSE BOARD X,
4 months ago
Math,
11 months ago
Geography,
11 months ago
India Languages,
11 months ago